Efektivitas Pemakaian Metode Ekspositori untuk Meningkatkan Kemandirian Belajar Siswa SMP Kota Bekasi - Sara Sahrazad; Maria Cleopatra (Jurnal Ilmiah Wahana Pendidikan, 2019)
Good learning must be supported by the right method and in accordance with the needs of students. Teachers continue to strive to develop methods that are compatible with the resources around the school and the area where students live. is one of the human needs as well as the basis for the existence of a society that can determine the structure of a society in an environment. In current learning, there are still various problems that arise due to communication. In this case including teachers, students and school principals Activities will be held from the beginning of September to December 2018. Researchers try to see the problems that exist in junior high schools. The author sees that students tend to be less independent in doing school assignments. For that we need special formulas and methods that can improve students' independence. One of them is the expository method. This researcher uses quantitative research methods, with normality and homogeneity test and T test, processing using SPSS 21. The results of the study show that, there are differences in the value results, before using the expository method, there is an increase in the expository method usage. and there is a significant effect of the expository method on the learning independence of SMP Azzuhriyah students